Impact of virtual cash economy on livelihood outcomes of informal cross border traders in Gweru, Zimbabwe - Dzawanda, Beauty; Nicolau, Melanie D.; Matsa, Mark (Springer, 2022)
Informal Cross Border Trade (ICBT) is a viable economic activity for many people, in Zimbabwe, who have depended on it for survival during economic hardships. Due to climate change, agriculture cannot be depended upon for survival and people are increasingly depending on ICBT for a livelihood. Despite a crucial role in providing for many, ICBT has been negatively affected by changes in the fiscal economy, specifically, the adoption of virtual cash in a time of cash crisis. This paper examines the impact of the virtual cash economy on the livelihood of participants in ICBT in Gweru, Zimbabwe. Qualitative data was collected and subjected to inductive analysis. Results revealed a positive livelihood outcome for traders prior to the virtual cash economy, followed by a negative outcome when virtual cash payments increased. The paper presents a framework that highlights the importance of cash, to ensure the success and sustainability of ICBT in the city of Gweru. The paper concludes with the recommendation that ICBT should be integrated into policy to address identified issues that affect economic benefits of ICBT, to ensure its sustainability in the provision of essential livelihood needs in line with Sustainable Development Goals.